Tanzania [in Strategies and priorities for African agriculture] - Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2012)
Despite its poor performance during the 1980s and 1990s, Tanzania’s economy expanded rapidly after the turn of the century, with national gross domestic product (GDP) growing at 6.6 percent per year during 1998 –2007 (Tanzania, MFEA 2008). This rate was almost double the average growth rate achieved in the previous decade; between 1990 and 1995 the recorded growth was only 2.7 percent, after which it steadily improved to reach 5 percent per year by 2000. Recent economic growth also appears to have been relatively broadly based. Although the newly established gold-mining sector recorded the highest growth rates during 1998–2007, it was the large agriculture and manufacturing sectors that contributed the most to national growth.